Assessing the impact of micro-credential training in higher education: A pilot study supporting BA dissertations - Martín Gilete, Marta; Blanco García, Cristina (European Public & Social Innovation Review, 2024)
Introduction: Micro-credentials, endorsed by the European Union for enhancing lifelong learning and employability, offer targeted, flexible learning experiences. This pilot study investigates the impact of integrating micro-credential training into the BA dissertation process for English Studies students at the University of Extremadura. Methodology: The study involved a two-week, in-person micro-credential course, divided into modules on time management, research techniques, and writing skills, supplemented by pre- and post-training surveys to assess students’ needs and the training’s short-term and long-term impact. Seven fourth-year students participated in the study, providing feedback through surveys. Results: The training improved students’ preparedness, confidence, and motivation. Key areas of development included time management, research skills, and emotional resilience. Students reported sustained benefits, applying the skills and strategies learned throughout their dissertation process. Discussion: Findings highlight the training’s positive short-term and long-term impacts, including increased motivation and practical skill application. However, it identifies areas for improvement, such as more training in citation techniques and writing clarity. Conclusions: Micro-credential training effectively addresses gaps in traditional curricula, enhancing students’ readiness for their BA dissertations. Further research with larger cohorts and diverse disciplines is recommended to generalise the findings and refine the microlearning approach.